ANALISIS EFISIENSI TEKNIS USAHATANI PADI DI DESA SUNGAI RENGAS KECAMATAN SUNGAI KAKAP: PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Saputra, Zaky Farid; Imelda, Imelda; Kusrini, Novira (Institute of Computer Science (IOCS), 2025)
Rice is a strategic commodity that plays a vital role in national food security. However, productivity in several regions of Indonesia, including Kubu Raya Regency, remains relatively low due to inefficient input use. This study aims to analyze the technical efficiency of rice farming and the socioeconomic factors influencing it in Sungai Rengas Village, Sungai Kakap District. The study used a survey method with 65 farmer respondents selected purposively. Input-oriented Data Envelopment Analysis was applied with Constant Return to Scale (CRS) and Variable Return to Scale (VRS) assumptions, while Tobit regression was used to examine the influence of socioeconomic factors on the level of technical efficiency. The results showed an average technical efficiency of 0.823 in the CRS model and increased to 0.908 in the VRS model, with some farmers having achieved full efficiency. An analysis of the efficiency scale shows that the majority of farmers are in the Increasing Returns to Scale (IRS) stage, indicating potential for increased output through additional inputs. Tobit regression results revealed that age significantly negatively impacted efficiency, while superior seed type significantly positively impacted technical efficiency. This study confirms that increased efficiency can be achieved through the selection of superior seeds, more proportional input management, and adjustments to the farming scale.